Human Papillomavirus Infection as a Possible Cause of Spontaneous Abortion and Spontaneous Preterm Delivery - Lea Maria Margareta Ambühl; Ulrik Baandrup; Karen Dybkær; Jan Blaakær; Niels Uldbjerg; Suzette Sørensen (Hindawi Limited, 2016)
Based on the current literature, we aimed to provide an overview on Human Papillomavirus prevalence in normal pregnancies and pregnancies with adverse outcome. We conducted a systematic literature search in PubMed and Embase. Data extracted from the articles and used for analysis included HPV prevalence, pregnancy outcome, geographical location, investigated tissue types, and HPV detection methods. The overall HPV prevalence in normal full-term pregnancies was found to be 17.5% (95% CI; 17.3-17.7) for cervix, 8.3% (95% CI; 7.6-9.1) for placental tissue, 5.7% (95% CI; 5.1-6.3) for amniotic fluid, and 10.9% (95% CI; 10.1-11.7) for umbilical cord blood. Summary estimates for HPV prevalence of spontaneous abortions and spontaneous preterm deliveries, in cervix (spontaneous abortions: 24.5%, and preterm deliveries: 47%, resp.) and placenta (spontaneous abortions: 24.9%, and preterm deliveries: 50%, resp.), were identified to be higher compared to normal full-term pregnancies (P<0.05 and P<0.0001). Great variation in HPV prevalence was observed between study populations of different geographical locations. This review demonstrates an association between spontaneous abortion, spontaneous preterm delivery, and the presence of HPV in both the cervix and the placenta. However, a reliable conclusion is difficult to draw due to the limited number of studies conducted on material from pregnancies with adverse outcome and the risk of residual confounding.